Licensing Contracts: Control Rights, Options, and Timing - Crama, Pascale; De Reyck, Bert; Taneri, Niyazi (Management Science, 2017)
Research and development (R&D) collaborations, common in high-tech industries, are challenging to manage because of technical and market risks as well as incentive problems. We investigate how control rights, options, payment terms, and timing allow the innovator to capture maximum value from its R&D collaborations with a marketer. Our study reveals a counterintuitive result; the innovator may, under certain conditions, prefer to grant launch control rights or buyout options to the marketer despite the fact that both terms restrict its downstream actions. We demonstrate that a menu of contracts is not necessary to address the adverse selection problem because the menu can be replicated by a single option contract. We show that timing, through renegotiation or delayed contracting, as well as the careful allocation of control rights and options can have a significant influence on the value of collaborative R&D. We provide recommendations on the optimal contract structure and timing based on two project characteristics, novelty of the R&D process and market-potential variability. This paper was accepted by David Hsu, entrepreneurship and innovation.